Where the moon isn't [large type] - Filer, Nathan (Thorndike Press large print core series., 2014)
While on vacation with their parents, Matthew Homes and his older brother snuck out in the middle of the night. Only Matthew came home safely. Ten years later, Matthew tells us, he has found a way to bring his brother back. What begins as the story of a lost boy turns into a story of a brave man yearning to understand what happened that night, in the years since, and to his very person.